Distributed generation in unbundled electricity markets - Johannes Wagner (Institute of Energy Economics at the University of Cologne (EWI), 2018)
Electricity systems are increasingly characterized by distributed generation technologies, e.g. rooftop photovoltaic systems, which are used by end consumers to directly produce electricity. Additionally, empirical evidence suggests that electricity retailers exercise market power in many unbundled electricity markets. Against this backdrop this articles analyzes the impact of distributed generation on imperfect retail markets for electricity in a spatial competition framework. I find that distributed generation puts competitive pressure on retailers and induces lower retail prices. Therefore even consumers who do not use distributed generation benefit. Based on this effect regulators can shift welfare to consumers by subsidizing distributed generation in order to position it as a competitor to grid based electricity. However, if only a limited share of demand can be supplied with distributed generation, there is a point at which retailers disregard the substitutable share of demand and focus on the non-substitutable consumption in order to realize higher mark-ups. As a result, increased subsidies for distributed generation can increase retail prices and harm consumers. With optimal subsidies this strategy of retailers is prevented by limiting usage of distributed generation.
Keywords: D43; L13; L50; L94; Q48; 330; Distributed generation; renewable energy; retail unbundling; spatial competition